EVALUASI JARDIKNAS DALAM PENGEMBANGAN TEKNOLOGI INFORMASI SEBAGAI SARANA PEMBELAJARAN DI KABUPATEN GUNUNGKIDUL - , Mohammad Ridwan Hanafi, S. Pd ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Educational institutions have invested heavily on the utilization of Information and Communication Technology (ICT) and had a major impact in the context of universities, organizations and in teaching methods. The effectiveness the impact of technology on student achievement attracts the attention of all stakeholders. Many academic researchers are trying to answer that question on the theoretical and empirical levels. The population in this study were all high schools, both vocational and general, which has been 22 schools connected with Jardiknas phase 1 in Gunungkidul. Instead, this study used Percentage Analysis of of tabulated data according to criteria. Percentage frequency distribution is shown in the form of a table containing the results of the percentage of each observation for each data point or grouping. The results showed that the utilization of aspects of group Jardiknas Vocational School (SMK), the majority of schools in the state of passive utilization (58.3%) where access Jardiknas be used only by the teacher. It is unfortunate that the current utilization status actually get the smallest portion is 21.4%. A similar picture occurred in the group High School (SMA) in which the majority was still in the state of passive utilization (37.5%) and the status of the active utilization also get the smallest portion is 22.7%. In the context of access Jardiknas utilization rate in relation to school performance based on the percentage of unsuccessful National Exam, the study found that